Performance of sFlt-1/PlGF ratio ≥85 for ruling in preeclampsia within 4 weeks - Cerdeira, AS; O’Sullivan, J; Ohuma, EO; James, T; Papageorghiou, AT; Knight, M; Vatish, M (Elsevier, 2020)
Objective Preeclampsia (PE) is a complex and heterogeneous disorder of pregnancy. Current clinical diagnostic criteria are nonspecific and correlate poorly with adverse fetal and maternal outcomes. The recently introduced angiogenic biomarkers soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) are used in Europe as an aid in the management of patients with a suspected disease. They have been shown to improve risk stratification, time to diagnosis, and outcomes.1, 2, 3 Widespread sFlt-1 or PlGF use in Europe followed the publication of the PROGNOSIS study,4 which showed a very high negative predictive value of the sFlt-1–to–PlGF ratio cutoff of 38 (99.3%; 95% confidence interval [CI], 97.9–99.9) for patients presenting with a suspected disease between 24 0/7 and 36 6/7 weeks’ gestation. A ratio of ≤38 is now used to rule out PE and safely discharge patients with a suspected disease.3 However, the reported positive predictive value (PPV) for a ratio of >38 ruling in PE in the following 4 weeks was low (PPV=36.7%; 95% CI, 28.4–45.7), which is less than optimal for clinical decision making.4 A higher cutoff could be more appropriate as a rule in. A cutoff of ≥85 has been associated with the development of adverse outcomes in patients with suspected PE5 and has also been suggested as an aid in the diagnosis3; however, its performance was not assessed in the PROGNOSIS study. Therefore, we evaluated the performance of the sFlt-1–to–PlGF ratio cutoff of ≥85 for ruling in PE within 4 weeks in patients with a suspected disease. Study Design This is a posthoc analysis of the INSPIRE trial,1 a randomized clinical trial assessing the use of the sFlt-1–to–PlGF ratio in women with suspected PE (n=370). Our population is similar to that of the PROGNOSIS study: patients with suspected disease and with a similar prevalence of PE (23%). Patients who presented with suspected PE between 24 0/7 and 36 6/7 weeks’ gestation had an sFlt-1–to–PlGF ratio test performed and were assigned to reveal (test results known to clinicians) or nonreveal (results unknown) trial arms.1 The primary endpoint of the INSPIRE clinical trial was admission within 24 hours of the test. Secondary endpoints of the INSPIRE trial were PE and other maternal and fetal adverse outcomes.1 The predictive performance of the sFlt-1–to–PlGF ratio cutoff of 85 was assessed by calculating the sensitivity, specificity, PPV, and respective 95% CIs. Results The PPV of the sFlt-1–to–PlGF ratio of ≥85 for ruling in PE within 4 weeks was 71.4% (95% CI, 51.3–86.8), significantly higher than the reported 36.7% (95% CI, 28.4–45.7) for a cutoff of 38 (Table).